Modelling the Effect of Heavy Metals on the Growth Rate of Enterobacter sp. Strain Neni-13 on SDS (Journal of Environmental Microbiology and Toxicology, 2018)
The SDS-degrading bacterium Enterobacter sp. strain Neni-13 was strongly inhibited by mercury. Growth of the SDS-degrading bacterium at various concentrations of mercury shows a sigmoidal pattern with lag periods ranging from 7 to 10 h. As the concentration of mercury was increased, the overall growth was inhibited with 1.0 g/L causing an almost cessation of bacterial growth. The growth rates obtained from the modified Gompertz model was then modelled according to the modified Han-Levenspiel, Wang, Liu, modified Andrews and the Amor models. Out of the five models, only Wang, modified Han-Levenspiel and the Liu models were able to fit the curve, whilst the modified Andrews and Amor models were unable to fit the curves. Both the Wang and modified Han-Levenspiel models show acceptable fitting while the Liu model shows poor fitting. Results of the statistical analysis showed that the Wang model was the best model based on the lowest values for RMSE and AICc, highest adjusted correlation coefficient (adR2) and values of AF and BF closest to unity. The parameters obtained from the Wang model, which are Ccrit, ïmax and m which represent critical heavy metal ion concentration (g/l), maximum growth rate (g/l h) and empirical constant values were 0.216 (95%, confidence interval f 0.193 to 0.239), 1.05 (95%, confidence interval of 0.938 to 1.167) and 0.389 (95%, confidence interval of 0.148 to 0.636) respectively.
Keywords: SDS-degrading, Enterobacter sp., metal inhibition model, mercury, Wang